Sosialisasi Pencegahan Diabetes Bersama Tropicana Slim Kepada Masyarakat Kelurahan Lateri, Kota Ambon - Jusuf Leiwakabessy; Debiyanti De Fretes (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Diabetes is a non-communicable disease. Diabetes is one of the most common chronic diseases in the world and is characterized by increased levels of glucose in the body. This metabolic disease occurs as a result of insufficient insulin secretion. Considering that every person has the right to have, to live a healthy, sustainable and prosperous life. The main target of this activity is the Lateri Village community. Socialization activities are carried out using 1 method, which is power point presentation of material. The specific objectives of implementing socialization to prevent diabetes with Tropicana Slim include increasing awareness of safe, healthy and sustainable living, as well as bringing positive changes in sustainable lifestyle behavior patterns by consuming Tropicana Slim products to stabilize sugar levels in the body.